Protein Carbonyl as a Biomarker of Oxidative Stress in Severe Leptospirosis, and Its Usefulness in Differentiating Leptospirosis from Dengue Infections - Fernando, Narmada (PLoS One, 2016)
Pathogenesis of disease severity in leptospirosis is not clearly understood whether it is due to direct damage by pathogen or by adverse immune responses. Knowledge on biomarkers of oxidative stress which could be used in identifying patients with severe illness has shown to be of great value in disease management. Thus, the main aim of this study was to assess the damage to serum proteins and lipids, and their significance as biomarkers of oxidative stress in severe leptospirosis. In regions endemic for both leptospirosis and dengue, leptospirosis cases are often misdiagnosed as dengue during dengue epidemics. Therefore, the second aim was to assess the potential of the oxidative stress markers in differentiating severe leptospirosis from critical phase dengue. We measured serum antioxidants (uric acid and bilirubin), total antioxidant capacity (AOC), protein carbonyl (PC) and lipid hydroperoxide (LP) in patients with severe leptospirosis (n = 60), mild leptospirosis (n = 50), dengue during the critical phase (n = 30) and in healthy subjects (n = 30). All patient groups had similar total antioxidant capacity levels. However, the presence of significantly high uric acid and total bilirubin levels may reflect the degree of renal and hepatic involvement seen in severe leptospirosis patients (p<0.02). Serum PC and LP levels were significantly higher in leptospirosis patients compared to critical phase dengue infections (p<0.005). Moreover, high serum PC levels appear to differentiate SL from DC [area under the curve (AUC) = 0.96; p<0.001]. Serum PC may be a reliable biomarker of oxidative damage to serum proteins to identify severe leptospirosis patients (AUC = 0.99) and also to differentiate severe leptospirosis from mild cases (AUC = 0.78; p<0.005) indicating its contribution to pathogenesis. Use of serum PC as an indicator of leptospirosis severity and as an oxidative stress biomarker in differentiating leptospirosis from dengue would provide the opportunity to save lives via prompt patient management.